Natural resource management : towards better integration : poverty reduction and sustainable livelihoods in Bangladesh, mainstreaming natural resource management into policies, institutions & processes - Workshop on Natural Resource Management: Towards Better Integration (2002 : Dhaka, Bangladesh); Bangladesh Centre for Advanced Studies; Great Britain. Department for International Development, Bangladesh (Dhaka : Bangladesh Centre for Advanced Studies, 2003)
Papers presented at the workshop.
Includes bibliographical references.
Keywords: Natural resources -- Bangladesh -- Congresses; Environmental policy -- Bangladesh -- Congresses